Dilated cardiomyopathy: the role of genetics, highlighted in a family with Filamin C (FLNC) variant. Issue 9 (20th August 2021) - Dungu, Jason N; Langley, Samantha G; Hardy-Wallace, Amy; Li, Brian; Barbagallo, Rossella M; Field, Duncan; Homfray, Tessa; Savage, Henry Oluwasefunmi
Abstract : Dilated cardiomyopathy (DCM) is a heterogenous group of disorders characterised by left ventricular dilatation and dysfunction, in the absence of factors affecting loading conditions such as hypertension or valvular disease, or significant coronary artery disease. The prevalence of idiopathic DCM is estimated between 1:250 and 1:500 individuals. Determining the aetiology of DCM can be challenging, particularly when evaluating an individual and index case with no classical history or investigations pointing towards an obvious acquired cause, or no clinical clues in the family history to suggest a genetic cause. We present a family affected by DCM associated with Filamin C variant, causing sudden cardiac death at a young age and heart failure due to severe left ventricular impairment and myocardial scarring. We review the diagnosis and treatment of DCM, its genetic associations and potential acquired causes. Thorough assessment is mandatory to risk stratify and identify patients who may benefit from primary prevention implantable cardioverter defibrillator therapy according to international guidelines. Genetic testing has some limitations, and is positive in only 20%–35% of DCM, but should be considered in specific cases to identify families who may benefit from cascade screening after appropriate counselling. The management of often complex familial cardiomyopathy requires specialist input for every case, and the appropriate infrastructure to coordinate investigations.